Historical analysis of the contribution of public policies to the humanization of the healthcare system in Chile - Pavlovic Jeldres, Sebastián; Tapia Escobar, Eric; Riveros Jiménez, Marcela; Mellado, Augusto; Silva-Jiménez, Diego; León, Francisco (Acta Bioethica, 2025)
The objective of this research was to analyze the historical contribution of public policies to the humanization of the healthcare system in Chile between 2004 and 2024. The methodology was a historical analysis of official documents from the Ministry of Health and its dependent agencies. The results show progressive advances in the regulatory recognition and promotion of principles such as dignity, respect, empathy, and participation in healthcare, especially since the enactment of Law 20.584 in 2012. However, gaps remain in implementing these policies, related to staff training, infrastructure, process adequacy, patient empowerment, and control systems. It is concluded that public policies have played a crucial role in establishing humanization as a central axis of the Chilean health system over the last two decades. It is recommended that mechanisms for enforcing rights be strengthened, training in relational skills intensified, a person-centered model be moved toward, resources for its implementation should be allocated, intersectoral initiatives coordinated, and research should be encouraged.